Augmented Reality Kekarangan Bali dengan Natural Feature Tracking (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
The carving art that developed in Bali has very distinctive characteristics and can make Balinese carving easily recognizable, among others, from several combinations of leaf, fruit, and flower motifs in very beautiful convex and concave shapes. Balinese carving is generally divided into three parts, namely Keketusan, Pepatran and Kekarangan. The lack of information about Kekarangan Bali makes people less aware of the forms and meanings contained in the Kekarangan Bali due to the limited distance and time to be able to learn Kekarangan Bali directly. Because of this we need Augmented Reality (AR) as a solution to be used as props in helping to introduce Kekarangan Bali more specifically using the Natural Feature Tracking (NFT) method because it can directly apply feature detection and then give a descriptor at every angle detected on the target image that is visible in the real environment so that the application of Augmented Reality (AR) is not fixated on a predetermined target image to be able to display objects 3D.